Generation Z Oversharing and Vulnerability to Online Gender-Based Violence: A Phenomenological Study of Instagram - Musfiah Saidah; Nadya Kharima; Mehnaz Gul (HUMANISMA : Journal of Gender Studies, 2026)
This research examines the phenomenon of gender-based violence in online media, particularly as it emerges through the practice of oversharing among Generation Z on the Instagram platform. The problem addressed is the increasing cases of gender-based violence rooted in the excessive disclosure of personal information in digital spaces. The novelty of this study lies in its focus on Generation Z’s oversharing behavior as a factor that triggers vulnerability to gender-based violence in online media. This study employs a qualitative method with a case study approach and in-depth interviews with both male and female informants who are active Instagram users. The findings reveal that oversharing behavior not only increases the risks of harassment, bullying, and exploitation but also introduces new dynamics in Generation Z’s digital interaction patterns. The discussion emphasizes the need for digital literacy, privacy awareness, and more adaptive user protection policies to mitigate the potential for gender-based violence in online media. Thus, this study contributes to the field of digital communication and gender studies in Indonesia.